Biological Control of Bacterial Wilt in South East Asia - Triwidodo Arwiyanto (Universitas Gadjah Mada, 2014)
Bacterial wilt disease caused by Ralstonia solanacearum destroys many crops of different plant families in South East Asia despite many researches about the disease, and the availability of developed control method in other parts of the world. There is no chemical available for the bacterial wilt pathogen and biological control is then chosen as an alternative to save the crops. Most of the biological control studies were based on antagonism between biological control agent and the pathogen. The biological control agents were intended to reduce the initial inoculum of the pathogen. The effort to minimize the initial inoculum of the pathogen by baiting with the use of hypersensitive host-plant was only reliable when conducted in the greenhouse experiments. Various microorganisms have been searched as possible biological control agents, for instance avirulent form of the pathogen, soil or rhizosphere bacteria (Bacillus spp. and fluorescent pseudomonads), actinomycetes (Streptomyces spp.), yeast (Pichia uillermondii, Candida ethanolica), and a consortium of microorganisms known as effective microorganisms (EM). None of these biological control agents has been used in field application and they need further investigation in order to effectively control bacterial wilt. Opportunities and challenges in developing biological control to combat bacterial wilt are discussed in the paper.Penyakit layu bakteri yang disebabkan oleh Ralstonia solanacearum menghancurkan banyak tanaman dalam famili yang berbeda di Asia Tenggara meskipun telah banyak penelitian tentang metode pengendaliannya. Penyakit ini sulit dikendalikan karena banyaknya variabilitas patogen dan belum tersedianya sumber ketahanan yang mapan. Di samping itu, sampai saat ini belum ada bahan kimia yang tersedia untuk patogen layu bakteri ini sehingga pengendalian biologi kemudian dipilih sebagai cara alternatif untuk menyelamatkan tanaman. Sebagian besar penelitian pengendalian biologi didasarkan pada antagonisme antara agen pengendalian biologi dan patogen. Agen pengendalian biologi tersebut dimaksudkan untuk mengurangi inokulum awal patogen. Upaya untuk meminimalkan inokulum awal patogen dengan umpan dengan menggunakan tanaman inang sangat rentan hanya dapat diandalkan ketika dilakukan dalam percobaan rumah kaca. Berbagai mikroorganisme telah diteliti kemungkinannya sebagai agensia pengendalian biologi seperti bentuk avirulen dari patogen, bakteri tanah atau bakteri rizosfer (Bacillus spp. dan pseudomonad fluorescen), actinomycetes (Streptomyces spp.), khamir (Pichia guillermondii, Candida ethanolica), dan konsorsium mikroorganisme yang dikenal sebagai EM (Effective Microorganisms). Meskipun demikian tidak satupun agensia pengendalian biologi ini sampai pada taraf aplikasi lapangan sehingga diperlukan penelitian lebih lanjut. Peluang dan tantangan dalam mengembangkan pengendalian biologi untuk memerangi penyakit layu bakteri dibahas pada tulisan ini.